Pentingnya Peran Keluarga dalam Proses Rehabilitasi Pasien dengan Gangguan Jiwa - Pragholapati, Andria; Wardany, Nadia Sintia; Amalia, Linda; Dharmansyah, Dhika; Darmawati, Irma; Nasution, Lina Anisa; Fitriana, Lisna Anisa; Somantri, Budi; Salasa, Sehabudin; Andriyani, Septian (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2025)
Mental disorders are among the health problems that affect all aspects of an individual's life. The rehabilitation of patients with mental disorders does not rely solely on professional services in healthcare facilities, but is also greatly influenced by family involvement. The family plays a crucial role in supporting the healing process, preventing relapse, and optimizing the patient's quality of life. Unfortunately, many families still lack an understanding of their strategic role in this process. This community service activity aims to improve families' knowledge and skills in supporting the rehabilitation of patients with mental disorders. The methods used include education, discussion, simulation, and direct family mentoring. The results showed an increase in family understanding of patient care, active involvement in behavior monitoring, and improved emotional management. Family-based interventions have proven to be an effective approach in the sustainable rehabilitation process of patients with mental disorders.